Application Of Audio Visuals On Knowledge And Attitude Of Adolescent Men Regarding Personal Hygiene To Prevent Pityriasis Versicolor - Amalia, Dhea; Simanjuntak, Farida Mentalina; Karo, Marni Br (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Pityriasis versicolor or tinea versicolor is skin disease caused by a fungus that causes itching. This disease usually arises from dirty environments, dirty bathrooms and poor environmental sanitation. Someone who doesn't care about their personal hygiene tends to be more susceptible to skin disease. Personal hygiene is influenced by knowledge, culture, attitudes, socio-economic status, personal choices and socioeconomics. Using the same towel at the As-Suruur Islamic Middle School boarding house, after playing sports, not changing clothes is habit of teenagers due to lack of knowledge. Audio visuals is one of the efforts to increase knowledge and attitudes so that personal hygiene can be implemented well. The aim of this research is to see the effect of implementing Audio Visual on the knowledge and attitudes of young men regarding personal hygiene to prevent Pityriasis Versicolor at As-Suruur Islamic Middle School. This research used a quantitative design using 62 samples and was designed using a Quasi-Experimental design with a One Group Pretest-Posttest design. The results of the study showed that audio visual had significant effect on increasing knowledge, attitudes and application of personal hygiene to prevent tinea versicolor in As-Suruur Islamic Middle School students with p value of 0.000 (p value <0.05).